Ceramic oxidation protection coatings for refractory alloys from filler-loaded preceramic polymers: The role of particle size and volume fraction of particulate fillers. Issue 1 (July 2020) - Smokovych, I; Eley, H; Bosiaha, M; Scheffler, M
Abstract: Oxidation protection coatings on the base of perhydridopolysilazane (PHPS) polymer and Si/B filler materials were developed to prevent Mo-basis alloys against oxidation at 800 °C. Within this work the influence of the particle size and the volume fraction of particulate fillers on the oxidation protective effect of the coatings was investigated. Double and triple coatings were applied in order to determine the effect of layer thickness on the oxidation resistance properties.